Medina, A., Herrán, A. de la y Sánchez, C. (Coords.), V.V.A.A. (2011). Formación pedagógica y práctica del profesorado - Cabrera Cuevas, Jessica; Rodríguez Herrero, Pablo (Tendencias Pedagógicas, 2015)
Reseña